2020
DOI: 10.1186/s43019-020-00080-1
|View full text |Cite
|
Sign up to set email alerts
|

Is there an optimal age for total knee arthroplasty?: A systematic review

Abstract: Purpose The purpose of this systematic review was to elucidate the optimal age for patients undergoing total knee arthroplasty (TKA), to optimize the balance between the benefits and risks by analyzing patient-reported outcome measurements (PROM), revision rate, and mortality according to age. Materials and methods A rigorous and systematic approach was used and each of the selected studies was evaluated for methodological quality. Data were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 66 publications
2
29
0
2
Order By: Relevance
“…[3] It also reported that the proportion of patients more than 70 years old increased markedly from 48.1% (2010) to 61% (2018) [3]. In this study, the mean age of all participants (72.0 ± 5.8) was in the early 70s, which was recommended as an optimal age for TKA that could achieve the maximal passive range of motion (PROM) without increasing the revision or mortality rates [13]. A total of 60.2% lived in urban areas, 65.9% lived in Jeju city of current administrative districts, and 47.6% lived in Jeju city of formal administrative districts.…”
Section: Discussionmentioning
confidence: 73%
“…[3] It also reported that the proportion of patients more than 70 years old increased markedly from 48.1% (2010) to 61% (2018) [3]. In this study, the mean age of all participants (72.0 ± 5.8) was in the early 70s, which was recommended as an optimal age for TKA that could achieve the maximal passive range of motion (PROM) without increasing the revision or mortality rates [13]. A total of 60.2% lived in urban areas, 65.9% lived in Jeju city of current administrative districts, and 47.6% lived in Jeju city of formal administrative districts.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies focused on the analysis of postoperative e cacy and perioperative complications in patients of different ages after TKA [19,20]. Regardless of age, the satisfaction rate of knee surgery is more than 85%, and advanced age does not affect the e cacy of TKA [19].Other scholars have found that 70 years old is the best age for TKA [20]. There was no difference in the incidence of complications among patients younger than 75 years of age who received unilateral TKA or staged bilateral TKA [14].Different from previous studies, this study divided all patients undergoing SBTKA into age groups to study the incidence of complications in each group.…”
Section: Discussionmentioning
confidence: 99%
“…TKA has become an effective measure for the treatment of end-stage knee diseases, which can effectively improve joint function and relieve pain [1-3, 4-7, 19, 23, 26]. Previous studies focused on the analysis of postoperative e cacy and perioperative complications in patients of different ages after TKA [19,20]. Regardless of age, the satisfaction rate of knee surgery is more than 85%, and advanced age does not affect the e cacy of TKA [19].Other scholars have found that 70 years old is the best age for TKA [20].…”
Section: Discussionmentioning
confidence: 99%
“…11 These occupations were categorized as three groups depending on their degree of physical work: non-manual workers (managers, professionals and related workers, and clerks), service or sales workers, and manual workers (skilled agricultural, forestry, shery, craft, and related trades workers, equipment, machine operating and assembling workers, and elementary workers). 12…”
Section: The Classi Cation Of Occupationmentioning
confidence: 99%